Unbalanced Magnetic Pull in Dual Three-Phase Machine - Drobnič, Klemen; Fišer, Rastko (XXVIII. Symposium Electromagnetic Phenomena in Nonlinear Circuits (EPNC 2024): Conference Proceedings, 2025)
This paper examines the emergence of unbalanced magnetic pull (UMP) in dual three-phase permanent magnet synchronous machines (DTM) during post-fault (PFO) and synthetic loading operation (SLO). Through FEM (finite element method) simulations, the paper reveals that UMP arises due to interactions between field harmonics with differing spatial orders, specifically the 4th and 5th harmonics during PFO and SLO. The presence of both odd and even harmonics in the machine's field spectrum is identified as a critical factor in UMP generation. The simulation results confirm that while UMP in DTM increases bearing stress and reduces lifespan, it does not compromise mechanical integrity, providing insights for machine design and control strategies under PFO and SLO.